The Lorax - Seuss, Dr. (New York : Random House, 1971)
The Once-ler describes the results of the local pollution problem.
Elem. School Library Collection.
Kirkus Review.
School Library Media Quarterly (A.A.A.L.).
3.5.
3.5
K-3
Keywords: Pollution -- Fiction; Stories in rhyme; Pollution -- Fiction; Stories in rhyme